Essentials of WISC-V integrated assessment - Raiford, Susan Engi (Essentials of psychological assessment series., 2017)
"Practical, in-depth guidance for WISC-V and WISC-V Integrated assessment Essentials of WISC-V Integrated Assessment is the ideal companion for psychologists and other assessment professionals seeking helpful interpretive and practical information beyond the WISC-V and WISC-V Integrated published manuals. Beginning with an overview of the test and its application to educational intervention, this book provides in-depth information on new administrative, scoring, and interpretation procedures specific to the WISC-V and the WISC-V Integrated. Insider access to the WISC-V and WISC-V Integrated standardization data allows the reader to derive new WISC-V composite scores unavailable from other resources. Readers of this book are the first to receive access to these new composite scores, which are designed to be more appropriate for children with expressive language difficulties and motor impairments. The reader also receives exclusive access to four new WISC-V expanded index scores that provide broader measures of visual spatial ability, working memory, auditory working memory, and processing speed. Significant advances in working memory research demand more comprehensive assessment of children with a broader range of abilities and limitations. The reader will learn how to perform a highly comprehensive assessment of working memory with the WISC-V and the WISC-V Integrated. A digital interpretive tool automatically calculates the new composite scores, completes the relevant comparisons, and generates interpretive information for new comparisons to streamline the reporting process. The WISC-V Integrated serves to expand and clarify WISC-V results by helping practitioners better understand a child's cognitive processes and the reasons for low or discrepant performance. This book helps practitioners get more out of the WISC-V and the WISC-V Integrated, with indispensable guidance and practical tools. Understand the WISC-V Integrated and its proper application to the development of educational interventions Learn how administration, scoring, and interpretation has changed for retained subtests, how to administer and score new subtests, and how to obtain the first-ever composite scores Discover how to use the WISC-V and WISC-V Integrated to assess both auditory and visual working memory, and how to obtain an unparalleled and in-depth picture of working memory along a continuum of cognitive complexity Learn how to adjust WISC-V use for children with expressive or motor difficulties Explore alternative composite scoring based on the WISC-V and WISC-V Integrated standardization data to increase utility for specific populations The WISC-V Integrated is an essential component of the WISC-V assessment process, and Essentials of WISC-V Integrated Assessment is the ideal guide for practitioners"--